2022
DOI: 10.1039/d2ra02472a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the optoelectronic response of highly correlated Cu3P photocatalyst

Abstract: The optical absorption from BSE@PBE0 is in better agreement with the experiment than BSE@DFT+U. The electron–hole interaction and strong correlation between electrons play a vital role in the optoelectronic response of Cu3P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, these materials have been found to exhibit lower photocatalytic activity compared to TiO 2 , a well‐known and widely used photocatalyst. Yet there is a class of potential photocatalysts with low band gap such as SnS, Bi 2 S 3 [14] and Cu 3 P [15] . It is observed that there are not many studies focused on the theoretical aspects of most semiconductors in this class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these materials have been found to exhibit lower photocatalytic activity compared to TiO 2 , a well‐known and widely used photocatalyst. Yet there is a class of potential photocatalysts with low band gap such as SnS, Bi 2 S 3 [14] and Cu 3 P [15] . It is observed that there are not many studies focused on the theoretical aspects of most semiconductors in this class.…”
Section: Introductionmentioning
confidence: 99%
“…However, these materials have been found to exhibit lower photocatalytic activity compared to TiO 2 , a well-known and widely used photocatalyst. Yet there is a class of potential photocatalysts with low band gap such as SnS, Bi 2 S 3 [14] and Cu 3 P. [15] It is observed that there are not many studies focused on the theoretical aspects of most semiconductors in this class. One such exception in this case is Cu 3 P that have been both theoretically and experimentally investigated, the primary focus of these studies was to determine its electrical and optical response.…”
Section: Introductionmentioning
confidence: 99%